Molybdenum disulfide nanoflower-carbon nanotube-polyether-ether-ketone composite material and preparation method thereof
By adding molybdenum disulfide nanoflower-carbon nanotube hybrid material to polyether ether ketone, the molybdenum disulfide nanoflower-carbon nanotube-polyether ether ketone composite material was prepared, which solved the wear problem of polyether ether ketone in friction parts, and significantly improved the compression performance, hardness and friction-reduction and wear resistance of the material.
Patent Information
- Application Number
- CN202411939001.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-26
AI Technical Summary
Polyether etherketone is prone to wear in friction parts such as radial bearings, and has poor friction reduction and wear resistance.
Molybdenum disulfide nanoflower-carbon nanotube hybrid material was added to polyether ether ketone, and the hybrid material was prepared through a one-step hydrothermal reaction, and ultrasonic dispersion, ball milling and hot-pressing molding were carried out with polyether ether ketone to prepare the molybdenum disulfide nanoflower-carbon nanotube-polyether ether ketone composite material.
The compression performance, hardness and friction-reduction and wear resistance of composite materials have been significantly improved, with an average friction coefficient reduced by 16.95%-23.73%, abrasion volume reduced by 82.20%-87.07%, a compression strength increased by 12.04%-16.54%, and a surface hardness increased by 3.17%-3.75%.
Smart Images

Figure CN119735936A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of composite materials, and in particular to a molybdenum disulfide nanoflower-carbon nanotube-polyetheretherketone composite material and a preparation method thereof. Background Art
[0002] At present, polyetheretherketone (PEEK) has been widely used in aerospace, automobile manufacturing, medical equipment and other fields due to its excellent thermal stability, dimensional stability, mechanical strength, chemical stability and processing performance. However, with the rapid development of modern industrial technology, the requirements for material performance are also constantly increasing. For example, when polyetheretherketone is used for friction parts such as radial bearings and bearing bushings, it is easy to wear under load conditions, and the friction reduction and wear resistance effect is poor. Summary of the invention
[0003] In view of the deficiencies of the above-mentioned related technologies, the purpose of the present application is to provide a molybdenum disulfide nanoflower-carbon nanotube-polyetheretherketone composite material and a preparation method thereof, by adding molybdenum disulfide nanoflower-carbon nanotube hybrid material to polyetheretherketone to improve the compression performance and hardness of the molybdenum disulfide nanoflower-carbon nanotube-polyetheretherketone composite material while improving the friction reduction and wear resistance effect.
[0004] On the one hand, the present application provides a molybdenum disulfide nanoflower-carbon nanotube-polyetheretherketone composite material adopts the following technical solution:
[0005] A molybdenum disulfide nanoflower-carbon nanotube-polyetheretherketone composite material is prepared from the following components in parts by weight: 97-99 parts of polyetheretherketone and 1-3 parts of molybdenum disulfide nanoflower-carbon nanotube hybrid material.
[0006] Preferably, the molybdenum disulfide nanoflower-carbon nanotube hybrid material is obtained by mixing a precursor and carbon nanotubes and subjecting them to a one-step hydrothermal reaction.
[0007] Preferably, the precursor comprises a molybdenum precursor and a sulfur precursor.
[0008] Preferably, the weight ratio of the molybdenum precursor to the carbon nanotubes is 0.2-4:1.
[0009] Preferably, the weight ratio of the molybdenum precursor to the carbon nanotubes is 0.268-1.35:1.
[0010] Preferably, the weight ratio of the molybdenum precursor to the carbon nanotubes is 0.68:1.
[0011] Preferably, the weight ratio of the molybdenum precursor to the sulfur precursor is 1:1-3.
[0012] Preferably, the weight ratio of the molybdenum precursor to the sulfur precursor is 1:2.
[0013] Preferably, the molybdenum precursor includes one or both of ammonium molybdate tetrahydrate and ammonium dimolybdate.
[0014] Preferably, the molybdenum precursor is ammonium molybdate tetrahydrate.
[0015] Preferably, the sulfur precursor includes one or more of thiourea, ammonium thiocyanate and sodium thiosulfate.
[0016] Preferably, the sulfur precursor is thiourea.
[0017] Preferably, the carbon nanotubes include one or both of multi-walled carbon nanotubes and single-walled carbon nanotubes.
[0018] Preferably, the carbon nanotubes are multi-walled carbon nanotubes.
[0019] On the other hand, the present application provides a method for preparing a molybdenum disulfide nanoflower-carbon nanotube-polyetheretherketone composite material using the following technical solution:
[0020] A preparation method of a molybdenum disulfide nanoflower-carbon nanotube-polyetheretherketone composite material comprises the following steps: mixing a precursor, a surfactant and a carbon nanotube to perform a one-step hydrothermal reaction to obtain a molybdenum disulfide nanoflower-carbon nanotube hybrid material, mixing the molybdenum disulfide nanoflower-carbon nanotube hybrid material, polyetheretherketone powder and a solvent to obtain a mixture by ultrasonic dispersion, and then drying, ball milling the mixture and then drying, and finally hot pressing to obtain the molybdenum disulfide nanoflower-carbon nanotube-polyetheretherketone composite material.
[0021] Preferably, the surfactant includes one or more of cetyltrimethylammonium bromide, dodecyldimethylbenzylammonium chloride and octadecyldimethylhydroxyethylammonium nitrate.
[0022] Preferably, the surfactant is cetyltrimethylammonium bromide.
[0023] Preferably, the solvent is ethanol, and the ultrasonic dispersion time is 5-40 min.
[0024] Preferably, the solvent is ethanol, and the ultrasonic dispersion time is 15 min.
[0025] Preferably, the temperature of the hot pressing molding is 350-370° C., the pressure is 5-10 MPa, and the holding time is 0.5-1.5 h.
[0026] Preferably, the temperature of the hot pressing molding is 360° C., the pressure is 7 MPa, and the holding time is 1 hour.
[0027] In summary, the present application includes at least one of the following beneficial technical effects:
[0028] 1. Compared with polyetheretherketone, the average friction coefficient of the molybdenum disulfide nanoflower-carbon nanotube-polyetheretherketone composite material is reduced by 16.95%-23.73%, the wear loss is reduced by 82.20%-87.07%, the compression strength is increased by 12.04%-16.54%, and the surface hardness is increased by 3.17%-3.75%. The compression performance and hardness of the molybdenum disulfide nanoflower-carbon nanotube-polyetheretherketone composite material are improved while the friction reduction and wear resistance are improved;
[0029] 2. Compared with carbon nanotube-polyetheretherketone composite materials, the average friction coefficient reduction rate of molybdenum disulfide nanoflower-carbon nanotube-polyetheretherketone composite materials is 10.26%-17.58%, the wear reduction rate is 43.71%-59.11%, the compression strength increase rate is 4.92%-9.13%, and the surface hardness increase rate is 0.65%-1.22%. The compression performance and hardness of molybdenum disulfide nanoflower-carbon nanotube-polyetheretherketone composite materials are improved while the friction reduction and wear resistance effect is improved;
[0030] 3. The raw materials of the molybdenum disulfide nanoflower-carbon nanotube-polyetheretherketone composite material of the present application are easy to obtain, the preparation method is simple, the conditions are mild, no special equipment is required, and no high-concentration chemical reagent modification or coupling agent is required to improve the dispersibility of additives. It is green and environmentally friendly while reducing the preparation cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 is a scanning electron microscope image of the molybdenum disulfide nanoflower-carbon nanotube hybrid material in Example 1 of the present application;
[0032] Figure 2 This is a scanning electron microscope image of the molybdenum disulfide nanoflower-carbon nanotube hybrid material in Example 5 of the present application. DETAILED DESCRIPTION
[0033] The present application is further described in detail below in conjunction with examples. The following examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention. In the following examples, if specific conditions are not specified, they are carried out according to normal conditions or conditions recommended by the manufacturer. The methods used are conventional methods known in the art unless otherwise specified, and the consumables and reagents used are commercially available unless otherwise specified. Unless otherwise specified, the professional and scientific terms used herein have the same meaning as those familiar to those skilled in the art. In addition, any method or material similar or equivalent to the recorded content may also be applied to the present invention.
[0034] The raw materials used in the examples and comparative examples can all be obtained commercially.
[0035] Example 1
[0036] Example 1 of the present application provides a molybdenum disulfide nanoflower-carbon nanotube-polyetheretherketone composite material, which is prepared by the following steps: Preparation of molybdenum disulfide nanoflower-carbon nanotube hybrid material: 0.2247g of ammonium molybdate tetrahydrate, 0.4494g of thiourea and 0.0281g of hexadecyltrimethylammonium bromide are added to 40mL of deionized water as molybdenum precursor, sulfur precursor and surfactant respectively, stirred for 30min, and then 0.33g of multi-walled carbon nanotubes (MWCNTs) are added, stirred and ultrasonically treated for 20min to obtain a mixed solution. The mixed solution is poured into a 100mL reactor for a hydrothermal reaction, and the reaction parameters are as follows: heating to 220°C at a rate of 1°C / min, maintaining the temperature for 24h, and then slowly cooling to room temperature at a rate of 0.4°C / min, filtering and washing to obtain a molybdenum disulfide nanoflower-carbon nanotube hybrid material.
[0037] Preparation of MoS2 nanoflower-carbon nanotube-polyetheretherketone composite material: Accurately weigh 98g polyetheretherketone powder and 2g MoS2 nanoflower-carbon nanotube hybrid material. Add the polyetheretherketone powder and MoS2 nanoflower-carbon nanotube hybrid material to ethanol, ultrasonically disperse for 15min and place on a magnetic stirrer, stir at 600rpm for 3h, then dry at 80℃ for 4h and at 100℃ for 2h to obtain a mixture. Add the mixture to a ball mill and ball mill at 300rmp for 4h, then dry in a drying oven at 120℃ for 3h to obtain a mixture, place the mixture in a mold, maintain pressure at 360℃ and 7MPa for 1h, and hot press to obtain a MoS2 nanoflower-carbon nanotube-polyetheretherketone composite material.
[0038] Example 2
[0039] Example 2 of the present application provides a molybdenum disulfide nanoflower-carbon nanotube-polyetheretherketone composite material. The difference between Example 2 and Example 1 is that, when performing the preparation step of the molybdenum disulfide nanoflower-carbon nanotube hybrid material, Example 2 uses 0.3371g of ammonium molybdate tetrahydrate, 0.6742g of thiourea, 0.0421g of hexadecyltrimethylammonium bromide and 0.25g of multi-walled carbon nanotubes.
[0040] Example 3
[0041] Example 3 of the present application provides a molybdenum disulfide nanoflower-carbon nanotube-polyetheretherketone composite material. The difference between Example 3 and Example 1 is that when performing the preparation step of the molybdenum disulfide nanoflower-carbon nanotube hybrid material, Example 3 uses 0.1685g of ammonium molybdate tetrahydrate, 0.3371g of thiourea, 0.0211g of hexadecyltrimethylammonium bromide and 0.38g of multi-walled carbon nanotubes.
[0042] Example 4
[0043] Example 4 of the present application provides a molybdenum disulfide nanoflower-carbon nanotube-polyetheretherketone composite material. The difference between Example 4 and Example 1 is that when performing the preparation step of the molybdenum disulfide nanoflower-carbon nanotube hybrid material, Example 4 uses 0.1124g of ammonium molybdate tetrahydrate, 0.2247g of thiourea, 0.0140g of hexadecyltrimethylammonium bromide and 0.42g of multi-walled carbon nanotubes.
[0044] Example 5
[0045] Example 5 of the present application provides a molybdenum disulfide nanoflower-carbon nanotube-polyetheretherketone composite material. The difference between Example 5 and Example 1 is that when performing the preparation step of the molybdenum disulfide nanoflower-carbon nanotube hybrid material, Example 5 uses 0.5056g of ammonium molybdate tetrahydrate, 1.0112g of thiourea, 0.0632g of hexadecyltrimethylammonium bromide and 0.13g of multi-walled carbon nanotubes.
[0046] Comparative Example 1
[0047] Comparative Example 1 provides a polyetheretherketone, which is prepared by the following steps: accurately weigh 100g of polyetheretherketone powder. Add the polyetheretherketone powder to ethanol, ultrasonically disperse it for 15min and place it on a magnetic stirrer, stir it at a speed of 600rpm for 3h, and then dry it at 80℃ for 4h and at 100℃ for 2h. Add the polyetheretherketone powder to a ball mill and ball mill it at 300rpm for 4h, and then dry it in a drying oven at 120℃ for 3h. Place the polyetheretherketone powder in a mold, maintain the pressure for 1h at a temperature of 360℃ and a pressure of 7MPa, and hot press it to obtain polyetheretherketone.
[0048] Comparative Example 2
[0049] Comparative Example 2 provides a carbon nanotube-polyetheretherketone composite material, which is prepared by the following steps: adding multi-walled carbon nanotubes to 40 mL of deionized water, stirring for 30 minutes, maintaining stirring and ultrasonic treatment for 20 minutes to obtain a mixed solution. The mixed solution is poured into a 100 mL reactor and heated to 220° C. at a rate of 1° C. / min, maintained at the temperature for 24 hours, and then slowly cooled to room temperature at a rate of 0.4° C. / min, filtered and washed, and the treated multi-walled carbon nanotubes are set aside.
[0050] Accurately weigh 98g of polyetheretherketone powder and 2g of multi-walled carbon nanotubes. Add polyetheretherketone powder and multi-walled carbon nanotubes to ethanol, ultrasonically disperse for 15 minutes and place on a magnetic stirrer, stir at 600rpm for 3h, then dry at 80℃ for 4h and at 100℃ for 2h to obtain a mixture. Add the mixture to a ball mill and ball mill at 300rpm for 4h, then dry in a drying oven at 120℃ for 3h to obtain a mixture, place the mixture in a mold, maintain pressure at 360℃ and 7MPa for 1h, and hot press to obtain a carbon nanotube-polyetheretherketone composite material.
[0051] Test and Inspection
[0052] (1) Scanning electron microscope imaging was performed on the molybdenum disulfide nanoflower-carbon nanotube hybrid materials in Example 1 and Example 5, and the scanning electron microscope images were as follows: Figure 1 and Figure 2 shown.
[0053] (2) The molybdenum disulfide nanoflower-carbon nanotube-polyetheretherketone composite materials prepared in Examples 1-5, the polyetheretherketone of Comparative Example 1, and the carbon nanotube-polyetheretherketone composite materials of Comparative Example 2 were subjected to the ISO
[0054] 604:2002 was tested for compression performance on a universal testing machine, with a sample size of 10×10×4 mm and a test condition of 1 mm / min. The test results are shown in Table 1 below.
[0055] (3) The molybdenum disulfide nanoflower-carbon nanotube-polyetheretherketone composite materials prepared in Examples 1-5, the polyetheretherketone of Comparative Example 1, and the carbon nanotube-polyetheretherketone composite materials of Comparative Example 2 were subjected to the ISO
[0056] 868 was tested for surface hardness on a Shore hardness tester. The sample size was 20×10×4mm. The test results are shown in Table 1 below.
[0057] Table 1:
[0058] Data Source Compression strength(MPa) Surface hardness (HD) Example 1 173.99 88.71 Example 2 168.12 88.28 Example 3 169.95 88.35 Example 4 167.28 88.21 Example 5 156.22 86.93 Comparative Example 1 149.3 85.5 Comparative Example 2 159.44 87.64
[0059] (4) A ball-disk reciprocating friction test was performed on the molybdenum disulfide nanoflower-carbon nanotube-polyetheretherketone composite materials prepared in Examples 1-5, the polyetheretherketone of Comparative Example 1, and the carbon nanotube-polyetheretherketone composite materials of Comparative Example 2 on an Rtec friction and wear testing machine. A GCr15 steel ball with a diameter of 6.3 mm was reciprocated with the molybdenum disulfide nanoflower-carbon nanotube-polyetheretherketone composite material of 20×10×4 mm. The test conditions were as follows: load 80 N, time 30 min, speed 6 Hz (linear speed 96 mm / s). The test results are shown in Table 2 below.
[0060] Table 2:
[0061] Data Source Average friction coefficient <![CDATA[Wear amount (10 -6 mm 3 / N·m)]]> Example 1 0.225 7.09 Example 2 0.233 9.24 Example 3 0.24 8.12 Example 4 0.245 9.76 Example 5 0.237 20.56 Comparative Example 1 0.295 54.83 Comparative Example 2 0.273 17.34
[0062] Results Analysis
[0063] The following is a combination of the experimental data provided in Table 1-2 and Figure 1-2 , describe this application in detail.
[0064] Referring to Table 1, the molybdenum disulfide nanoflower-carbon nanotube-polyetheretherketone composite materials of Examples 1-5 are significantly improved in compressive strength and surface hardness compared with the polyetheretherketone of Comparative Example 1 and the carbon nanotube-polyetheretherketone composite materials of Comparative Example 2. It shows that the addition of molybdenum disulfide nanoflower-carbon nanotube hybrid material is beneficial to improve the mechanical properties of polyetheretherketone and its composite materials. In particular, when the weight ratio of ammonium molybdate tetrahydrate to multi-walled carbon nanotubes is 0.68:1, the compressive strength of the molybdenum disulfide nanoflower-carbon nanotube-polyetheretherketone composite material of Example 1 is increased by about 16.54% (from 149.3MPa to 173.99MPa) compared with the polyetheretherketone of Comparative Example 1, and the surface hardness is also increased by 3.75% (from 85.5HD to 88.71HD), and the compressive strength and surface hardness of the carbon nanotube-polyetheretherketone composite material of Comparative Example 2 are also greatly improved. This indicates that the molybdenum disulfide nanoflower structure and carbon nanotube structure in the molybdenum disulfide nanoflower-carbon nanotube hybrid material prepared by regulating the ratio of molybdenum precursor and carbon nanotubes in the range of 0.2-4:1 have a synergistic effect in improving the mechanical properties of polyetheretherketone-based composites.
[0065] Referring to Table 2, the molybdenum disulfide nanoflower-carbon nanotube-polyetheretherketone composite materials of Examples 1-5 all showed lower friction coefficients and better wear resistance in the friction and wear test compared with the polyetheretherketone of Comparative Example 1 and the carbon nanotube-polyetheretherketone composite materials of Comparative Example 2. In particular, when the weight ratio of ammonium molybdate tetrahydrate to multi-walled carbon nanotubes was 0.68:1, the friction coefficient of the molybdenum disulfide nanoflower-carbon nanotube-polyetheretherketone composite material of Example 1 was reduced by about 23.73% (from 0.295 to 0.225) compared with the polyetheretherketone of Comparative Example 1, and the wear resistance was improved by 87.07% (the wear loss was from 54.83×10-6mm to 1.3mm). 3 / N·m is reduced to 7.09×10-6mm 3 / N·m), and the friction reduction and wear resistance of the carbon nanotube-polyetheretherketone composite materials of Examples 1-4 are also greatly improved compared with that of Comparative Example 2. This shows that the molybdenum disulfide nanoflower structure and the carbon nanotube structure in the molybdenum disulfide nanoflower-carbon nanotube hybrid material prepared by adjusting the ratio of the molybdenum precursor and the carbon nanotube in the range of 0.268-1.35:1 have a synergistic effect in improving the tribological properties of the polyetheretherketone-based composite material. Analysis shows that this may be because the MoS2 nanotube-CNT hybrid material forms a lubricating layer on the surface of the MoS2 nanotube-CNT-PEEK composite material, in which the MoS2 nanoflowers not only connect the MoS2 nanoflowers, but also increase the connection points between the multi-walled carbon nanotubes, thus avoiding the agglomeration of the two in the MoS2 nanotube-CNT-PEEK composite material as much as possible, thereby improving the stability of the lubricating layer structure. The combined effect improves the stability of the lubrication effect of the MoS2 nanoflowers and the multi-walled carbon nanotubes, thereby improving the friction reduction and wear resistance of the MoS2 nanotube-CNT-PEEK composite material.
[0066] The wear loss of the molybdenum disulfide nanoflower-carbon nanotube-polyetheretherketone composite material of Example 5 is slightly higher than that of the carbon nanotube-polyetheretherketone composite material of Comparative Example 2. The molybdenum disulfide nanoflower-carbon nanotube hybrid materials in Examples 1-5 are all hybrid structures in which molybdenum disulfide nanoflowers grow on multi-walled carbon nanotubes, among which Figure 1 It can be seen that the preparation of the hybrid material of molybdenum disulfide nanoflowers-carbon nanotubes in which molybdenum disulfide nanoflowers grow on multi-walled carbon nanotubes has been successfully achieved. In the hybrid material of molybdenum disulfide nanoflowers-carbon nanotubes in Example 1, the multi-walled carbon nanotubes form a uniform network structure at the bottom of the molybdenum disulfide nanoflowers, providing strong mechanical support, while the molybdenum disulfide nanoflowers grow on the surface of the multi-walled carbon nanotubes, with good adhesion and dispersion. Figure 2In Example 5, the number of molybdenum disulfide nanoflowers in the molybdenum disulfide nanoflower-carbon nanotube hybrid material is relatively large, while the number of multi-walled carbon nanotubes is relatively small, forming a structure dominated by molybdenum disulfide nanoflowers, and the multi-walled carbon nanotubes are sparsely distributed in the hybrid material. Analysis shows that this may be due to the large number of structural defects when the network structure formed by the multi-walled carbon nanotubes in the molybdenum disulfide nanoflower-carbon nanotube hybrid material of Example 5 supports or connects a large number of molybdenum disulfide nanoflowers, resulting in the wear resistance of the molybdenum disulfide nanoflower-carbon nanotube-polyetheretherketone composite material of Example 5 being lower than that of the molybdenum disulfide nanoflower-carbon nanotube-polyetheretherketone composite material of Examples 1-4.
[0067] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A molybdenum disulfide nanoflower-carbon nanotube-polyetheretherketone composite material, characterized in that: The invention is prepared from the following components in parts by weight: 97-99 parts of polyetheretherketone and 1-3 parts of molybdenum disulfide nanoflower-carbon nanotube hybrid material.
2. The molybdenum disulfide nanoflower-carbon nanotube-polyetheretherketone composite material according to claim 1, characterized in that: The molybdenum disulfide nanoflower-carbon nanotube hybrid material is obtained by mixing a precursor and carbon nanotubes and performing a one-step hydrothermal reaction.
3. The molybdenum disulfide nanoflower-carbon nanotube-polyetheretherketone composite material according to claim 2, characterized in that: The precursor includes a molybdenum precursor and a sulfur precursor.
4. The molybdenum disulfide nanoflower-carbon nanotube-polyetheretherketone composite material according to claim 3, characterized in that: The weight ratio of the molybdenum precursor to the carbon nanotubes is 0.2-4:
1.
5. The molybdenum disulfide nanoflower-carbon nanotube-polyetheretherketone composite material according to claim 3, characterized in that: The weight ratio of the molybdenum precursor to the sulfur precursor is 1:1-3.
6. The molybdenum disulfide nanoflower-carbon nanotube-polyetheretherketone composite material according to claim 3, characterized in that: The molybdenum precursor includes one or both of ammonium molybdate tetrahydrate and ammonium dimolybdate.
7. The molybdenum disulfide nanoflower-carbon nanotube-polyetheretherketone composite material according to claim 3, characterized in that: The sulfur precursor includes one or more of thiourea, ammonium thiocyanate and sodium thiosulfate.
8. A method for preparing the molybdenum disulfide nanoflower-carbon nanotube-polyetheretherketone composite material according to any one of claims 1 to 7, characterized in that: The following steps are involved: The precursor, surfactant and carbon nanotubes are mixed and subjected to a one-step hydrothermal reaction to obtain a molybdenum disulfide nanoflower-carbon nanotube hybrid material, the molybdenum disulfide nanoflower-carbon nanotube hybrid material, polyetheretherketone powder and a solvent are mixed and ultrasonically dispersed and then dried to obtain a mixture, the mixture is ball-milled and then dried, and finally hot-pressed to obtain the molybdenum disulfide nanoflower-carbon nanotube-polyetheretherketone composite material.
9. The method for preparing a molybdenum disulfide nanoflower-carbon nanotube-polyetheretherketone composite material according to claim 8, characterized in that: The solvent is ethanol, and the ultrasonic dispersion time is 5-40 minutes.
10. The method for preparing a molybdenum disulfide nanoflower-carbon nanotube-polyetheretherketone composite material according to claim 8, characterized in that: The temperature of the hot pressing molding is 350-370° C., the pressure is 5-10 MPa, and the holding time is 0.5-1.5 h.
Citation Information
Patent Citations
Molybdenum disulfide / graphene composite material and preparation method and application thereof
CN109256546A
Lubricating wear-resistant bearing bush and preparation method thereof
CN118931104A